Juana Bida change satirical skits on voters' education (Communication Foundation for Asia, 2010)
Communication Foundation for Asia's 2010 voters' education video that had become hit on Youtube. The episode "Demokrasya (OFF, BuY/FOOL the people)" shows Juana's concept of democracy changing as she pursues high political ambitions. From her idealism as a child, she becomes influenced by her politician father when she grows older and is exposed to fraud, graft and corruption. In the segment "Paano Ba Pumili", Juana Change interviews an applicant and bombards him with questions to gauge his qualifications and suitability for the position. We are challenged to be as meticulous in choosing our candidates. "Utang na Loob" is a parody of a silent movie, in which Juana Change is an ordinary citizen persuaded to vote for a local politician who offers promises of a new basketball court. This triggers dire consequences for her community. In "10 Commandments (ng Simpleng Panloloko)", Juana Change is a corrupt politician with her own version of how to win the elections using entertainment as well as exploitation, violence, graft and dirty tricks. "Protecting Your Vote" shows Juana Change as a voter who reminds us that our responsibility does not end after casting our ballot. She challenges us to be vigilant during the counting and even after the officials are elected. In "Kurapsyon ay Paglabanan", Juana Change tries her hand at interpreting a rap song which was a finalist in CFA's recent songwriting contest, challenging the youth to help fight for good governance.